Research on Noise Reduction of Electronic Expansion Valve based on Air-entrained Cavitation - Liu Shiyan; Liu Yicai; Zhang Yu; Wu Likang; Gong Zan (Zhileng xuebao)
While small household refrigeration equipment such as air conditioners and refrigerators provide a comfortable home environment, the associated noise has become one of the key reasons behind consumer complaints. This study uses the theory of air-entrained cavitation to optimize the structure of the electronic expansion valve. The refrigerant at the inlet of the evaporator is introduced to the outlet of the electronic expansion valve through the installation of a bypass pipe to increase the local pressure of the refrigerant, such that the bursting of bubbles in the two-phase flow can be effectively suppressed. The improved double-bypass electronic expansion valve and four-bypass electronic expansion valve may significantly reduce the noise generated by the refrigerant bubble burst at the outlet of expansion valves. Numerical simulation and experimental verification studies show that the double-bypass electronic expansion valve and four-bypass electronic expansion valve reduced noise by 2.729 dB(A) and 3.778 dB(A) than those of the original electronic expansion valve.